2004
DOI: 10.1097/00007632-200405150-00005
|View full text |Cite
|
Sign up to set email alerts
|

Innervation of the Lumbar Intervertebral Disc by Nerve Growth Factor-Dependent Neurons Related to Inflammatory Pain

Abstract: We found that most small neurons innervating the disc were CGRP-ir. Furthermore, disc inflammation caused an increase in CGRP-ir neurons but not IB4-binding neurons, suggesting that CGRP-ir, nerve growth factor-dependent neurons are more responsible for discogenic pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 22 publications
1
79
0
Order By: Relevance
“…However, the ratios of IB4-binding and P2X 3 receptor-IR neurons to FG-labeled neurons in L1 and L2 DRGs were higher than those in L3, L4 and L5 DRGs (P<0.01) GDNF receptor [6,26]. Aoki et al [3] have reported that rat intervertebral discs are innervated mostly by CGRP-IR NGF-dependent small neurons, and that disc inflammation caused an increase in CGRP-IR neurons, but not IB4-binding neurons, suggesting that CGRP-IR NGF-dependent neurons have an overriding responsibility for discogenic pain. Furthermore, it has also been reported that NGF and trkA-expressing nerve fibers are present in painful lumbar discs in humans [14].…”
Section: Characteristics Of Sensory Drg Neurons Innervating the Facetmentioning
confidence: 96%
See 1 more Smart Citation
“…However, the ratios of IB4-binding and P2X 3 receptor-IR neurons to FG-labeled neurons in L1 and L2 DRGs were higher than those in L3, L4 and L5 DRGs (P<0.01) GDNF receptor [6,26]. Aoki et al [3] have reported that rat intervertebral discs are innervated mostly by CGRP-IR NGF-dependent small neurons, and that disc inflammation caused an increase in CGRP-IR neurons, but not IB4-binding neurons, suggesting that CGRP-IR NGF-dependent neurons have an overriding responsibility for discogenic pain. Furthermore, it has also been reported that NGF and trkA-expressing nerve fibers are present in painful lumbar discs in humans [14].…”
Section: Characteristics Of Sensory Drg Neurons Innervating the Facetmentioning
confidence: 96%
“…We used four markers: (1) calcitonin gene-related peptide (CGRP) as a marker of small peptide containing neurons, (2) the glycoprotein binding the isolectin from Griffonia simplicifolia (IB4) or (3 the purinergic P2X 3 receptor for small, non-peptide containing neurons, and (4) neurofilament 200 (NF200) for small and large myelinated fibers. IB4-binding and CGRP and P2X 3 receptor containing neurons are typically involved in pain sensation, whereas NF200 is associated with pain and proprioception. Neurons innervating the L5/6 facet joints, retrogradely-labeled with fluorogold (FG), were distributed throughout DRGs from L1 to L5.…”
mentioning
confidence: 99%
“…(6,70,71) The most significant biochemical change to occur in DD is loss of proteoglycan. (72) The aggrecan molecules become degraded, with smaller fragments being able to leach from the tissue more readily than larger portions.…”
Section: Molecular Mechanisms Of Iddmentioning
confidence: 99%
“…In addition it is an invasive procedure and it implies the injection of an adjacent normal disc to confirm a positive response. Therefore this diagnostic modality should be reserved for patients with presumed discogenic LBP who may be candidates for surgical treatment [57] due to its invasive nature and poor evidence for its sensitivity, specificity, and predictive value.…”
Section: Imaging the Intervertebral Discmentioning
confidence: 99%